2017
DOI: 10.1259/bjr.20170560
|View full text |Cite
|
Sign up to set email alerts
|

ABO blood group related venous thrombosis risk in patients with peripherally inserted central catheters

Abstract: Patients undergoing PICC insertion with a blood group B appear to have a higher risk of VT, independent of risks attached to the PICC procedure and cancer diagnosis. Without any existing guidelines for PICC-related VT, this investigation creates a platform for further research to be conducted in order to establish guidelines. Advances in knowledge: Previous studies investigating VT risk associated with blood group status related to large heterogeneous populations. In this article, we look at patients specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 21 publications
(24 reference statements)
1
17
0
2
Order By: Relevance
“…We found that PICC‐RT was associated with the diameter of the catheters (>4Fr), consistent with previous evidence (Chopra et al, 2017; Koo et al., 2018). Mechanically, larger PICC devices are more likely to cause endothelial damage and vascular reactivity as well as up‐regulate the coagulation process (Bahl et al., 2019; Song et al., 2020).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that PICC‐RT was associated with the diameter of the catheters (>4Fr), consistent with previous evidence (Chopra et al, 2017; Koo et al., 2018). Mechanically, larger PICC devices are more likely to cause endothelial damage and vascular reactivity as well as up‐regulate the coagulation process (Bahl et al., 2019; Song et al., 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Mechanically, larger PICC devices are more likely to cause endothelial damage and vascular reactivity as well as up‐regulate the coagulation process (Bahl et al., 2019; Song et al., 2020). For older patients, a 4‐Fr PICC has been the optimal choice (Chopra et al, 2017; Koo et al., 2018). For other patients, they can receive a PICC of different diameters such as 4‐Fr, 5‐Fr, and 6‐Fr.…”
Section: Discussionmentioning
confidence: 99%
“…Although this study is the first evaluation of these characteristics in MCs, the literature for PICCs supports the use of smaller diameter catheters as larger diameter catheters are associated with higher rates of CR thrombosis. [19][20][21] The relationship between the number of lumens and thrombosis is less conclusive. [22][23][24] Increase in contralateral arm thrombosis was an interesting finding of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of PICC-related venous thrombosis is 5%~20%, among which symptomatic PICCrelated venous thrombosis accounts for 1%~4%. 1,2,[4][5][6][7] Symptomatic venous thrombosis might result in a series of adverse consequences. ① Venous thrombosis may result in the following clinical manifestations: an enlarged arm circumference; reddening, flushing and swelling of the skin on the upper extremity; and tenderness at the catheter site or neighboring sites.…”
Section: Introductionmentioning
confidence: 99%